Effect of Educational Brochures on Preprocedural Anxiety in Pediatric Endoscopy: A Randomized Controlled Trial - Erel, Selin; Güleç Kılıç, Aslıhan; Camgöz Eryılmaz, Nuray; Toyran, Ülgen Öztürk; Eğritaş Gürkan, Ödül (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Preoperative anxiety is a common and significant issue in pediatric patients undergoing endoscopic interventions. The evaluation aimed to determine whether age-appropriate educational brochures could reduce anxiety in pediatric patients and their caregivers undergoing outpatient endoscopic procedures with sedation. Materials and Methods: Pediatric patients and their caregivers were randomly assigned to either a control group (standard verbal information only) or an intervention group (standard verbal information plus an age-appropriate educational brochure). On the day of the procedure, pediatric anxiety was assessed using the Modified Yale Preoperative Anxiety Scale (m-YPAS), whereas caregiver anxiety was measured using the Amsterdam Preoperative Anxiety and Information Scale (APAIS). Results: A total of 252 pediatric patients (age, 3-17 years; American Society of Anesthesiologists score, I-II) and their caregivers were recruited. Of these, 174 formed the control group and 78 received an educational brochure intervention. The demographic character istics were similar across the groups, except for caregiver age. While there were no significant between-group differences in caregiver APAIS scores, pediatric patients in the brochure group exhibited significantly lower m-YPAS scores (P < .05) than those in the control group. Conclusion: Providing children with age-appropriate educational brochures prior to sedation for endoscopic procedures significantly reduced their preoperative anxiety. This low-cost, easily implemented intervention may help improve procedural experience in pediatric patients and potentially enhance overall clinical outcomes. Cite this article as: Erel S, Kılıç AG, Eryılmaz NC, Toyran ÜÖ, Gürkan ÖE. Effect of educational brochures on preprocedural anxiety in pediatric endoscopy: A randomized controlled trial. Turk J Gastroenterol. 2025;36(10):680-691.